(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This Paper Examines Dirac Delta Impulse Control For Caputo Fractional Order Neural Network Having Time Varying Delay. With The Help Of An Appropriate Convex Lyapunov Function And Lmi Techniques, We Give Exponential Stability Conditions For The System. A Numerical Example Is Given To Show The Usefulness Of The Exponential Stability Conditions Obtained.